THE IMPACT OF MIGRANT WORKERS ON THE BEHAVIOR OF THE YOUNG GENERATION IN NAGARI SUNGAI NYALO IV KOTO MUDIEK - Vivi Gusmayani (JOURNAL INTERNATIONAL ON GLOBAL EDUCATION, 2022)
The success of migrant workers is reflected in the behavior of the young generation to mimic changes in migrant workers. Changes that are emulated are not only positive but also negative both from the economy and from a lifestyle that is no longer compatible with the local culture. This study aims to determine the changes in the lives of migrant workers and the impact of migrant workers on the behavior of the younger generation. The research method is qualitative. The research informants were determined by Purposive Sampling, totaling 13 people. Data is collected through observation, interviews and documentation studies. the validity of the data is determined by triangulation, the data are analyzed with the stages of reducing data, the presentation of data ang draws conclusions. The results of the study indicate a change in the lives of migrant workers such as economic improvement, how to dress and consumptive behavior. While the impact of changes to the behavior of young geberasi is to follow in the footsteps of migrant workers, imitate the manner of dress, lack of parental care for children, break up and get drunk. Conclusions about changes in migrant workers have an impact on the behavior of the younger generation, but not all young people imitate the changes in migrant workers.